Net Smelter Return Models and Their Use in the Exploration, Evaluation and Exploitation of Polymetallic Deposits - Goldie, Raymond; Tredger, Peter (Geoscience Canada, 1991)
Abstract As an aid in visualizing a mineral deposit, the three spatial dimensions are often reduced to two, by projection onto plans or sections.Similarly, the concentrations of different metals in the deposit can be represented in a single dimension through the use of a common denominator, the Net Smelter Return (NSR) per tonne. NSR is defined as the proceeds from the sale of mineral products after deducting off-site processing and distribution costs. In sulphide deposits in which the economic metals are principally copper, nickel, molybdenum or platinum group metals, a mine's receipts (the NSR) usually correspond to about 56%-60% of the gross value of the metals contained in the ore. This figure drops to around 40% for ores with significant quantities of lead or zinc. The presence of gold or silver in the ore will generally increase the sepercentages. An NSR model of a deposit is a representation which attempts to approximate the actual NSR which would be derived from exploitation of the mineralization being modelled. NSRs are calculated from estimates of grades, recoveries, concentrate treatment schedules and commodity prices. With the advent of cheap, readily available computer processing, it is now practicable for geologists to routinely use NSR models. At the exploration stage, NSR models provide a useful basis for presentation and comparison of drill-hole assays. At the evaluationstage of a project, NSR models are helpful inthe estimation of optimum grades, recoveries, and production rates. At the exploitation stage, NSR models provide a rigorous basis for grade control. A widely used alternative to the NSR pertonne as a common denominator, the "equivalent grade" (e.g., "gold-equivalent" or "cop-per-equivalent"), is misleading and should be avoided.